High-throughput single-cell transcriptomics on organoids. (February 2019) - Brazovskaja, Agnieska; Treutlein, Barbara; Camp, J Gray
Abstract : Three-dimensional (3D) tissues grown in culture from human stem cells offer the incredible opportunity to analyze and manipulate human development, and to generate patient-specific models of disease. Methods to sequence DNA and RNA in single cells are being used to analyze these so-called 'organoid' systems in high-resolution. Single-cell transcriptomics has been used to quantitate the similarity of organoid cells to primary tissue counterparts in the brain, intestine, liver, and kidney, as well as identify cell-specific responses to environmental variables and disease conditions. The merging of these two technologies, single-cell genomics and organoids, will have profound impact on personalized medicine in the near future.